2005
DOI: 10.3801/iafss.fss.8-315
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Of Performance-based Requirements For Structural Design

Abstract: The paper presents how actions can be assessed for a performance-based structural fire safety design from the first formulations in the building program to the final derivations of the fire load to be applied for each structural member. In order to indicate what is of importance for the assessment of the requirements, a couple of simple analyses of structural response are made. The examples are chosen deliberately to show the difference between a traditional design based on standard fire resistance and a perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The cooling phase has consistently been demonstrated to be important in terms of structural strength. For example, Hertz performed an experimental study for a fully developed fire scenario and tested the strength concrete column, it was found that load bearing capacity of column decreased by half during flaming phase and other half in cooling phase [51].…”
Section: Standard Fire Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooling phase has consistently been demonstrated to be important in terms of structural strength. For example, Hertz performed an experimental study for a fully developed fire scenario and tested the strength concrete column, it was found that load bearing capacity of column decreased by half during flaming phase and other half in cooling phase [51].…”
Section: Standard Fire Curvesmentioning
confidence: 99%
“…According to Hertz, "safe design" of a structure in terms of fire depends on two important questions: first, if the building is allowed to collapse during fire (which is generally never an acceptable criterion set by a code) or not, second; if the stakeholders rely on the fire brigade [51]. It is through stakeholder agreement that the performance requirements are set.…”
Section: Performance Levelmentioning
confidence: 99%
“…It is noted in Dr. Babrauskas' letter that he views the cool down phase of heating to be a non-problem. The authors would like to highlight that there have been experiments where cool down has been shown to be a vulnerability to structures [11][12][13][14] and also in real structures [15]. The inclusion of the cool down phase acknowledges the delay in heat propagation through materials (including combustible ones), and this allows for a more thorough analysis of the structural behaviour after the peak fire temperatures has been reached.…”
mentioning
confidence: 99%